THE EFFECT OF WORK DISCIPLINE AND WORKLOAD ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A VARIABLE INTERVENING AT PT. SUCOFINDO MEDAN BRANCH - Intan Febrizi Nasution; Yeni Absah; Syahyunan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
The purpose of this study is to testfactors that affect employee performance at PT. SUCOFINDO Medan Branch seen from Work Discipline, Workload and Job Satisfaction. The population in this study were all employees at PT. SUCOFINDO Medan Branch. The sample selection used in this study amounted to 44 people. The data analysis technique used was the measurement model (outer model) and inner model consisting of convergent validity, discriminant validity, model coloniality test, composite reliability, path coefficient, and R-Square which were processed using SEM - PLS (Structural Equation Modeling - Partial Least Square). The results of this study indicate that: 1) work discipline affects employee performance, 2) workload affects employee performance, 3) job satisfaction affects employee performance, 4) work discipline affects job satisfaction, 5) workload affects job satisfaction, 6) work discipline affects performance with job satisfaction as an intervening variable, 7) workload affects performance with job satisfaction as an intervening variable.